He Became What We Are: A Patristic and Dogmatic Analysis of the Incarnation as the Path to Theosis - Andrew Lucas Tjong; Yohanes Bambang Cahyo Wicaksono (Journal Of Spirituality And Practical Theology, 2026)
The doctrine of the Incarnation has often been treated as a historical or abstract Christological doctrine, while its soteriological, ecclesiological, and anthropological significance within the Eastern Orthodox tradition has received comparatively limited attention, particularly in Indonesian theological scholarship. This article re-examines the Eastern Orthodox understanding of the Incarnation through a qualitative library study employing patristic and dogmatic theological approaches by analyzing the writings of the Eastern Church Fathers together with Orthodox dogmatic sources. The study argues that, for the Church Fathers and later Orthodox theologians, Christology is inseparable from soteriology, and that the hypostatic union serves not merely as a doctrinal definition but as the theological foundation of theosis, through which humanity participates in the divine life. The findings demonstrate that the Incarnation integrates Christological, Trinitarian, ecclesiological, liturgical, and anthropological dimensions into a unified vision of salvation centered on humanity's restoration and communion with God. By re-centering the Incarnation on its soteriological purpose, this study contributes to contemporary theological discourse by highlighting the enduring relevance of Eastern Orthodox theology for interdenominational dialogue and for addressing the secularization of Christmas.